Challenges and Strategies in Teaching English Speaking Skills to Young Learners: Perspectives of Teachers in Indonesia - Laila, Fitri Nur; Adityarini, Hepy; Maryadi, Maryadi (VELES Voices of English Language Education Society, 2023)
This research explores the challenges and strategies associated with teaching English speaking skills to young learners in Indonesia, focusing on students learning English as a second or foreign language. The study aims to understand the specific obstacles faced by teachers in this context and to identify effective methods for overcoming these challenges. Employing a qualitative case study approach, the research involved five elementary English teachers selected through purposive sampling. Data collection was conducted through interviews and observations, followed by thematic analysis to interpret the findings. The study also emphasized ensuring data quality through the establishment of trustworthiness. The findings revealed five key issues impacting the teaching of English-speaking skills to young learners in Indonesia. Challenges stemming from the students included inhibition, negative attitudes towards learning English, and low participation rates. From the teachers' perspective, difficulties in classroom management and the lack of a supportive English learning environment were identified as significant obstacles. To address these challenges, the teachers employed various strategies, including individualized instruction, use of translation, repetition techniques, and integrating games into the learning process. These approaches aimed to enhance student engagement and facilitate a more effective learning environment for developing English speaking abilities in young learners. The study's insights contribute to a better understanding of the complexities involved in teaching English as a second language in the Indonesian educational setting and offer practical solutions for educators facing similar challenges.